Problem of classification of semantic kernels of web resource - Orekhov, Sergey Valerievich; Malyhon, Hennadiy Vasilievich; Stratiienko, Nataliia Kostiantunivna (Національний технічний університет "Харківський політехнічний інститут", 2022)
The article presents a new theoretical basis for solving the problem of situational management of semantic cores identified on the basis of WEB content. Such a task arises within the framework of a new phenomenon called virtual promotion. Its essence lies in the fact that a real product can exist in two realities: online and offline. According to marketing theory, the lifetime in two realities is the same. However, in the online mode, the goods exist independently and in accordance with the laws of the use of Internet technologies. Therefore, based on the concept of a marketing channel, it was proposed to consider a message in such a channel as a semantic core. The core is a specially selected set of keywords that briefly describe the product and the corresponding need. It has been proposed that each need forms a so-called class of need. Therefore, the product description will either belong to this class or not. In addition, a product can be described by a different set of keywords, which means that different descriptions of the same product or several products, if there are any for sale in the enterprise, will fall into the demand class. As a result, in this work, it was proposed to consider the center of this class as the so-called K-candidate. It is the K-applicant that will be the semantic core that will be considered at the current iteration of the situational management process. In addition, in order to move from one situation to another, in other words, from one core to another, it is required to have such an alternative core. It can be safely taken either from the neighborhood of the need class center (K-applicant), or the center of another class (another K-applicant), if the product can cover several needs of a potential buyer. Then the actual task is to classify the classes of needs based on the text corpus in HTML format. Having a text corpus at the first stage, the task of synthesizing semantic cores is realized, and then the classification task itself. This article proposes the formulation of the classification problem, taking into account the features that the Internet technologies contribute to search engine optimization. In particular, it is proposed to use four metrics from the category of WEB statistics. And then it is proposed to use the clustering method to identify classes of needs, taking into account the fact that the K-applicant is presented as a semantic network or as a graph.

У У статті представлено нову теоретичну базу для вирішення задачі ситуаційного управління семантичними ядрами, виділеними на основі ВЕБ контенту. Таке завдання виникає у рамках нового феномена під назвою віртуальне просування. Суть його полягає в тому, що реальний товар може існувати у двох реальностях: онлайн та офлайн. Відповідно до теорії маркетингу час життя у двох реальностях одне й теж. Однак у режимі онлайн товар існує самостійно і згідно із законами застосування Інтернет технологій. Тому в роботі на основі концепції маркетингового каналу було запропоновано розглядати повідомлення у такому каналі як семантичне ядро. Ядро є спеціально виділене безліч ключових слів, які коротко описують товар та відповідну йому потребу. Було запропоновано, кожна потреба формує так званий клас потреби. Отже, опис товару або належатиме даному класу чи ні. З іншого боку, товар можна описати іншим набором ключових слів, отже у клас потреби потраплять різні описи однієї й тієї ж товару чи кількох товарів, якщо такі є для підприємства продажу. В результаті в цій роботі було запропоновано вважати центр такого класу так званим К-претендентом. Саме К-претендент і буде тим семантичним ядром, яке на поточній ітерації процесу ситуаційного управління розглядатиметься. Крім того, для переходу від однієї ситуації до іншої, тобто від одного ядра до іншого, потрібно мати таке альтернативне ядро. Його можна сміливо брати або з околиці центроїду класу потреби (Кпретендента), або центроїд іншого класу (інший К-претендент), якщо товар може покрити кілька потреб потенційного покупця. Тоді актуальне завдання класифікації класів потреб на основі текстового корпусу у форматі HTML. Маючи текстовий корпус першому етапі реалізується завдання синтезу семантичних ядер, та був власне завдання класифікації. У цій статті запропоновано постановку завдання класифікації з урахуванням особливостей, що вносять Інтернет технології, пов’язані з пошуковою оптимізацією. Зокрема, запропоновано використовувати чотири метрики з розряду ВЕБ статистики. І далі запропоновано використовувати метод кластеризації для виділення класів потреб з урахуванням того, що К-претендент представлений як семантична мережа або як граф.
Задача класифікації семантичних ядер веб ресурсу
Keywords: semantic kernel; Ford – Fulkerson method; keyword; K-applicant; ключове слово; метод Форда – Фалкерсона; семантичне ядро; К-претендент